The Effect of Cross-section and Elliptical Hole Ratio on Crashworthiness Parameters of Crash-Box Structure - Warsiyanto, Budi Aji; Widanto, Muhammad Hadi; Musthofa, Ilham; Maulana, Ichsan; Sitompul, Sahril Afandi; Yuniarti, Endah (Indonesian Journal of Aerospace, 2021)
The thin-walled column structure or crash-box with metal material and consisting of multi-cell were found to be much more efficient in energy absorption than single-cell under axial impact loads. In this study, a numerical analysis was performed using the Abaqus finite element method for the cross-section differences in thin-walled column structures. The cross-section differences are compared to get a configuration that complies with the indicator parameters using the complex proportional assessment (COPRAS) method. The chosen cross-section configuration is further enhanced by creating elliptical holes with different diameter ratios. The results show that the thin-walled column structure with nine-cell cross-section accompanied by an elliptical hole ratio of 0.3 indicates the potential corresponding to the indicator parameters for the crashworthiness application.